The Impact of Tinnitus Severity on Work Functioning among U.S. Military Veterans with Tinnitus - Coco, Laura; Hooker, Elizabeth R.; Gilbert, Tess A.; Harker, Graham R.; Clark, Khaya D.; Reavis, Kelly M.; Henry, James A.; Zaugg, Tara L.; Carlson, Kathleen F. (Seminars in Hearing, 2023)
Tinnitus is highly prevalent among military Veterans. Severe tinnitus can be associated with negative impacts on daily life. Veterans with severe tinnitus may also have greater difficulties in functional roles, including work. However, few studies have explicitly explored this relationship. Traumatic brain injury (TBI), also prevalent among Veterans, is associated with tinnitus and can additionally impair work functioning. This quantitative investigation used a population-based survey to assess the relationship between tinnitus severity, measured using the Tinnitus Functional Index (TFI), and the impact of tinnitus on work, measured using a composite score from the Tinnitus History Questionnaire, among a stratified random sample of VA healthcare-using Veterans diagnosed with tinnitus, with and without comorbid TBI. Analyses were weighted to account for sampling design and Veteran non-response; multiple imputation was used to account for missing data. Results indicated that for every 1-point increase in TFI score, there was an average 8% increase in the odds of reporting a high level of impact on work functioning (OR: 1.08; 95% CI: 1.06, 1.11). Veterans with a comorbid TBI diagnosis, compared with those without, were more likely to have high tinnitus-related impact on work functioning (OR: 2.69, 95% CI: 1.85, 3.91), but the relationship between tinnitus severity and the impact of tinnitus on work functioning did not differ by TBI status. These data can help researchers and clinicians understand complex symptoms experienced by Veterans with tinnitus, with and without TBI, supporting the improved provision of clinical services to these patients.
Keywords: disability; tinnitus; traumatic brain injury; Veterans; work functioning